Determination of Tannin Content of Gringsingan Stem Extract (Mesosphaerum suaveolens (L) Kuntze) by the UV-Vis Spectrophotometry - Handayani, Selpida; Aminah, Aminah; Nurliadi, Indah (Universitas Muslim Indonesia, 2025)
The Gringsingan plant (Mesosphaerum suaveolens (L.) Kuntze) is widely used in traditional medicine and is known for its diverse pharmacological properties. Traditionally, it has been utilized to treat various ailments such as tumors, malaria, headaches, cancer, fever, stomach pain, yellow fever, rheumatism, constipation, urethritis, diarrhea, and kidney disorders, as well as to act as an analgesic, antiseptic, antispasmodic, and depurative agent. The present study aimed to determine the total tannin content in the stem extract of Gringsingan obtained through Microwave-Assisted Extraction (MAE) and to evaluate its potential as a bioactive compound source. Microwave-assisted extraction was selected because of its advantages, including shorter extraction time, reduced solvent consumption, and efficient recovery of active compounds compared to conventional methods. This experimental research was conducted in the laboratory and consisted of several stages: sample preparation, qualitative testing for tannin presence, and quantitative determination of total tannin content. Qualitative identification using 1% FeCl₃ reagent produced a dark blue to greenish-black coloration, confirming the presence of tannins in the Gringsingan stem extract. The result was further supported by thin-layer chromatography (TLC) testing with the same reagent, which yielded consistent positive results. Quantitative analysis of the total tannin content was carried out using UV–Visible spectrophotometry, with absorbance measured at the maximum wavelength for gallic acid. The analysis revealed that the tannin concentration in the Gringsingan stem extract was 7.487 mg GAE/g extract, indicating that this plant possesses measurable levels of tannins that contribute to its traditional medicinal value.